Ottoman intelligence :|the second branch and its operational characteristics, 1914-1918 - Şimşeker, Somer Alp. (Thesis (Ph.D.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2021., 2021)
This study is about the Second Branch of the Ottoman Empire’s General Staff, which was originally established as a military intelligence institu tion and represented centralization tendency during the First World War. With the defeat in the Balkan Wars, the 1913 coup and the Martial Law administration along with the mobilization for the First World War, the Ministry of Defense became an important decision-making authority in the Ottoman Empire. These conditions contributed to the transfor mation of the Second Branch into a centralized structure in intelligence. With the Martial Law administration, the Second Branch carried out the duties of propaganda, censorship, domestic and foreign intelligence. Other intelligence institutions and their sources were canalized to the Second Branch, and all activities against espionage in the Empire was prohibited without its consent and the order. The control over propa ganda and censorship activities were given to the Second Branch. Prop aganda activities became a mortar of modern Turkey’s ideological infra structure. Second Branch gathered military, political and partly economic intelligence for foreign intelligence at the strategic, opera tional and tactical levels. The centralization tendency was assessed along with the administrative and organizational structure of the Sec ond Branch. This study contributes to the intelligence studies by pre senting a centralizing intelligence institution while many other states established separate institutions or new units regarding domestic and foreign intelligence during total war conditions.
Keywords: Intelligence service -- Turkey.; World War, 1914-1918.